Optimisation of high-resolution image simulations. I. Image selection in real space - Tang, D; Kirkland, A; Jefferson, D (1993)
A mathematical criterion for the selection of the optimum high-resolution image simulation is proposed, based on a comparison of simulated and experimental images in real space. The procedure is demonstrated using model experimental images of YBa2Cu3O7-x projected along the [010] direction for a range of experimental parameters. The more general possibility of the direct assessment of image similarity is also discussed. © 1993.